3x+3=7x-1

Simple and best practice solution for 3x+3=7x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+3=7x-1 equation:


Simplifying
3x + 3 = 7x + -1

Reorder the terms:
3 + 3x = 7x + -1

Reorder the terms:
3 + 3x = -1 + 7x

Solving
3 + 3x = -1 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
3 + 3x + -7x = -1 + 7x + -7x

Combine like terms: 3x + -7x = -4x
3 + -4x = -1 + 7x + -7x

Combine like terms: 7x + -7x = 0
3 + -4x = -1 + 0
3 + -4x = -1

Add '-3' to each side of the equation.
3 + -3 + -4x = -1 + -3

Combine like terms: 3 + -3 = 0
0 + -4x = -1 + -3
-4x = -1 + -3

Combine like terms: -1 + -3 = -4
-4x = -4

Divide each side by '-4'.
x = 1

Simplifying
x = 1

See similar equations:

| 2x-5=-30 | | 3x+x=1049 | | 7x-19=86 | | 4.5/.6.75= | | 1.2n-7=20 | | 0.2n-2=9 | | 2x-25y=-125 | | 0.125n-11=21 | | 0.12n-11=21 | | .12n-11=21 | | 3y+5y=12 | | 5n+6=41 | | -7(7+3x)=119 | | 2.4N+5=23 | | 4(n)+3=2n+8 | | 0.25n+5=25 | | k-2*4k=7-5k | | 17-(x+9)=7x-8 | | 4(3+5x)=-128 | | 42-5n=7 | | 4(x-6)+6=2(x-4) | | 6n-7=19 | | 9r+3=51r+10 | | 0.25n+3=8 | | 0.5n+3=18 | | 5(3x-6)=-210 | | 79-8n=15 | | p^2+3p+2=-1 | | 4n-15=9 | | 7(3+4x)=357 | | 8x-36=2x | | 2(-7+3x)=4 |

Equations solver categories